Reviewing the sacred object. Vassiliy Barskiy as the first Russian researcher of the Christian East - Yulia N. Buzykina (Российский журнал истории Церкви, 2020)
The article deals with the origins of the Russian Christian Archaeology namely with pilgrim notes of Vassiliy Barskiy. The author is reviewing Barskiy’s text as one of the first scientific descriptions of the sacred places, wonder-working icons and holy places. His descriptions of sacred objects are structured, they include illustrations, information from written and verbal sources as well as critics of these sources. He makes conclusions about relevance of information and relics themselves. Based on this, the author believes Vassiliy Barskiy schould be recognized not only one of the sources of Russian scientific tradition, but the first Christian archaeologist.